2012
DOI: 10.1161/circoutcomes.111.964700
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival and Recurrence After Acute Myocardial Infarction in England, 2004 to 2010

Abstract: Background— There are limited population-based national data on prognosis in survivors of acute myocardial infarction (AMI), particularly on long-term survival and the risk of recurrence. Methods and Results— Record linkage of hospital and mortality data identified 387 452 individuals in England who were admitted to hospital with a main diagnosis of AMI between 2004 and 2010 and who survived for at least 30 days. Seven years after an AMI, the risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
1
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(201 citation statements)
references
References 43 publications
9
174
1
17
Order By: Relevance
“…A British study evaluated long‐term survival of patients with MI who survived at least 30 days post‐index event. The median age of that study population was 71 years, and the 7‐year survival was 69% among men and 53% among women 13. In our landmark analysis conditioned upon surviving 1 year post‐MI, we observed an 8‐year mortality rate of 59%.…”
Section: Discussionmentioning
confidence: 64%
“…A British study evaluated long‐term survival of patients with MI who survived at least 30 days post‐index event. The median age of that study population was 71 years, and the 7‐year survival was 69% among men and 53% among women 13. In our landmark analysis conditioned upon surviving 1 year post‐MI, we observed an 8‐year mortality rate of 59%.…”
Section: Discussionmentioning
confidence: 64%
“…Despite improvements in survival after the first and recurrent acute MI over the last three decades, individuals remain at high risk for recurrent events and death. A recent record linkage study [8] of long-term prognosis in England found that 86% of patients admitted to hospital for acute MI between 2004 and 2010 survived for at least 30 days. However, the 30 day survivors of both first and recurrent acute MI were, respectively, at 2 and 3 times higher risk of death from any cause compared with the general population for at least 7 years after the event.…”
Section: The Decision Problemmentioning
confidence: 99%
“…The relative risk was calculated using data from ATLAS-ACS 2-TIMI 51 trial on the relative number of ACS events compared to the number of ACS events in the first 6 months and an estimate of a relative risk after one year based on Smolina et al [8]. The relative risk declined over time so different values were calculated for each of the model tunnel states.…”
Section: Cost-effectiveness Evidencementioning
confidence: 99%
“…In particular, of those patients who develop a second AMI event, about one‐third will die 7, 8. Prevention of the recurrence of myocardial infarctions in patients with a history of AMI is important for improving prognosis.…”
Section: Introductionmentioning
confidence: 99%